PERANAN PENYIDIK KEPOLISIAN RESOR SIAK DALAM MENGUNGKAP TINDAK PIDANA MENGGUNAKAN SENJATA API - Benni Pernando S; Syaifullah Yophi A; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
In the beginning the use of firearms is only allowed for certain apparatus with the provisions and controls are tight, especially in the field of defence and security. As the development era that has begun to lack of surveillance conducted by law enforcement officers in cracking down on rampant circulation up illegal firearms that have been circulating in the community, which resulted in the occurrence of the crime using firearms. Licensing the ownership of firearms have been regulated in such a way in terms of legislation. Based on the description that has been described above, the author argues for the analytically descriptive regarding the role of the investigating of the Siak Resort Police in exposing the crime using firearms.This legal research suggests the outline of three problems as follows: 1) how did the Siak Resort Police investigator's role in exposing the crime using firearms?, 2) what are the obstacles of the Siak Resort Police investigator in exposing the crime using firearms?, and 3) how the Siak Resort Police investigator attempt to overcome the obstacles in exposing the crime using firearms? This research use sociological, juridical methods which are: applying research approaches to the study of perception and behavior of legal persons (human and legal entity) and the community as well as the effectiveness of the enactment of positive law in the community, where the author direct research on the location or place that is examined in order to give a complete and clear picture of the problems in a thorough the Siak Resort Police investigator's role in uncovering the crime using firearms.Legal research is then analyzed the role of the Siak Resort Police investigator in exposing the crime using firearms where the leading sector on Reserse Criminal Unit (Satreskrim) at the Siak Resort Police (Polres Siak) and coordinate with other entities such as the Security Intelligence Unit (Satintelkam) and the active participation of all elements of society, the obstacles encountered is the number of elements in the community who still feel frightened to report any event or incident a criminal offence who uses a firearm, and concrete efforts made by Police investigators, among others in the form of the Siak Resort Police construction and/or socialization to all elements of society to improve environmental safety systems in order to cope with the increasing swakarsa crime using firearms.